Spatial variation in the trophic structure of micronekton assemblages from the eastern tropical North Atlantic in two regions of differing productivity and oxygen environments. (September 2020) - Czudaj, Stephanie; Giesemann, Anette; Hoving, Henk-Jan; Koppelmann, Rolf; Lüskow, Florian; Möllmann, Christian; Fock, Heino O.
Abstract: The ecology of vertically migrating mesopelagic micronekton is affected by physical properties of their environment. Increased light attenuation in particle-rich productive waters, as well as low oxygen conditions decrease the migration amplitude. This likely has implications on the trophic organisation of micronekton communities, which are predominantly governed by niche partitioning in the vertical dimension. We investigated trophic structures of pelagic communities in the eastern tropical North Atlantic by comparing micronekton species assemblages from the low-oxygen region influenced by Mauritanian upwelling between 8° and 11° N (LO) and the less productive and more oxygenated equatorial area between 0 and 4°N (EQ). We analysed stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) in body tissues of 35 species of mesopelagic fishes, four species of cephalopods, two species of cnidarians, and two species of decapods and used these values as a proxy for their trophic niche and correlated them with the traits feeding guild, migration pattern, mean depth of occurrence and body size. Our results demonstrate significant regional differences in the food web structure and vertical trophic interactions of the investigated micronekton assemblages. Diurnally migrating fishes that predominantly feed on copepods exhibited higher δ 15 N values in the LO (9.6‰) than in the EQ (8.9‰), reflecting changes in baseline values of pelagic tunicates. Contrary, all other Feeding – Migrator guilds show lower or similar δ 15 N values in the LO compared to the EQ, indicating reduced isotopic enrichment between trophic levels (TL) in the LO compared to the EQ. Further, a generally lower δ 15 N enrichment between TL3 – TL4 compared to TL2 – TL3 was observed (LO: TL2 – TL3: 2.2‰, TL3 – TL4: 1.2‰; EQ: TL2 – TL3: 3.5‰, TL3 – TL4: 2.2‰). Quantitative isotopic niche metrics suggest enhanced competition in trophic niche space, whereas relative isotopic niche positions indicate an increased importance of food from lower trophic levels (non-crustacean and/or gelatinous prey resources) for fishes from the LO compared to the EQ. The absence of a depth-related increase in δ 15 N values of partial- and nonmigrators of the LO is contrary to results from the EQ and previously published data. Low δ 15 N values in partially and nonmigrating micronektonivores of the LO in comparison with those of the EQ could be due to feeding on lower trophic prey components in the LO, as is indicated by an overlap in isotopic niche with that of partially and nonmigrating mixed crustacean feeders in the LO. Alternatively, driving mechanisms could be the consumption of prey from shallower waters, regional differences in δ 15 N enrichment, species-specific ecological differences or a combination of these processes. Each of these explanations is likely tightly correlated to a vertical biogeochemical structuring effect of low oxygen midwater layers fuelled by high nitrate inputs from the Mauritanian upwelling region. Our study provides crucial ecological insights for a better understanding of large-scale gradients in micronekton migration patterns. Highlights: Micronekton ecology differed between equatorial (EQ) and low-oxygen waters (LO). The δ 15 N enrichment per trophic level was lower in the productive LO than in the EQ. Migrating fauna in the LO encounter increased competition for food resources. The δ 15 N values of non-migrators increased with depth in the EQ, but not in the LO. The δ 15 N values of mesopelagic micronektonivores were lower in the productive LO.